An Adequate Response to the Ecological Crisis - Joseph, Francis Xavier (Asian Horizons, 2024)
This paper focuses on analysing, in short, the Ecological Crisis at Present. At first, it introduces and explains the term crisis in relation to ecology and then it will further narrate to what extent this crisis has hit humanity. At this juncture, one could very well argue that the Ecological Crisis is a fruit that humanity is now reaping as a result of what it has been sowing for so many years. After having clarified the term crisis, the paper further discusses the response that is being made to tackle this crisis. The response can be found in two levels or two dimensions. The Society or the State The Religion or the Church How the above two realms have responded to this great ecological crisis of the present is argued in detail in two different sections. While the state implemented various rules and regulations in order to handle the situation, the Church issued various documents in order to conscientize its faithful and make an adequate and quick response to the great threat that has befallen on the humanity.